Moderate multiple parentage and low genetic variation reduces the potential for genetic incompatibility avoidance despite high risk of inbreeding - Tuni, Cristina; Goodacre, Sara; Bechsgaard, Jesper; Bilde, Trine (Public Library of Science, 2012)
Background